COVID-19 public health restrictions and opioid overdoes: a summative content analysis of emergency medical services records in three Texas counties - S. Scott Graham; Nandini Sharma; Tristin B. Hooker; Kimberlyn Harrison; Kasey Claborn (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background With the broad recognition of increased U.S. opioid overdose (OOD) rates between 2020 and 2021, media, public health, and healthcare organizations have raised significant concerns over the emergence of a simultaneous COVID-19-opioid “twindemic.” Research in this area has explored the possible relationships between negative externalities associated with the pandemic and/or COVID-19 public health interventions and increased risks for opioid use and overdose alongside diminished outcomes following OOD events. Methods The study offers a summative content analysis of Emergency Medical Service (EMS) responses to opioid overdose (OOD) events before and after the institution of COVID-19 restrictions. Specifically, the study investigates three Texas counties to evaluate changing OOD rates, patient demographics, and OOD event features. The analysis uses a previously validated machine learning tool to identify OOD events and conducted a summative content analysis of identified events. Results A total of 1170 OOD responses events were identified in the three-county dataset. This includes 874 in Travis County, 242 in El Paso County, and 54 in Williamson County. Each county experienced modest changes in EMS calls for OOD events between the pre-restriction and public health restriction time periods. Travis County’s OOD event rate declined from 454 to 420. El Paso’s increased from 103 to 139, and Williamson County’s increased from 23 to 31. These changes were not significant as percentage of possible OOD events or based on by-month comparison. The notable differences between pre-restriction and public health restriction periods were significant decreases in documentation of patient race/ethnicity in Travis and Williamson Counties, significant decreases in housing insecurity and use alone in Travis County, and an increase in transport refusal after treatment in the field in Travis County. Conclusions Ultimately the results presented here problematize prevailing analyses about the so-called opioid-COVID-19 “twindemic.” The data further support emerging trends about substantial geographic variation and show some ways that COVID-19 mitigation measures may have improved conditions for some populations, particularly in terms of housing security. Additionally, the results presented here indicate that further attention should be paid to the effects of first responder stress on documentation quality.